Developing Virtual Physics Practicum Module of Optic Based on Guided Inquiry to Improve Students' Science Process Skills - Yoga Budi Bhakti Bhakti; Ria Asep Sumarni; Sri Mayanty; Irnin Agustina Dwi Astuti (Journal of Science and Science Education, 2023)
Science process skills are one of the competencies that must be possessed by students after attending physics learning. Science process skills can be obtained by practicum activities both in person and virtually. However, the availability of virual physics practicum modules is not widely available in schools, even though there are some materials that cannot be done directly.  Therefore, a guided inquiry-based virtual practicum module is needed to improve students' science process skills in learning physics. This development research using 4-D method (Define, Design, Develop, and Disseminate). In the development of this module, the researchers only come to the third stage of the four stages. Validation results from experts get an average score of 86% interpretation which means that the module is included in the criteria worthy of use in learning even with the notes of experts to revise some of the components present in this module so that this module complies with existing standards. The results of the analysis of student responses to the practicum module obtained a total average of 85% with the category is "strong." This shows almost all the students gave a positive response to the virtual practicum module based guided inquiry. The development of virtual practicum modules based guided inquiry can improve science process skills of the students, with the average score of students‟ science process skills before using a virtual practicum module based guided inquiry of 2.63 and the average score of students‟ science process skills after using a virtual practicum module based guided inquiry of 3.30